Diffractogram data processing module for electronic journal. Finding diffraction maximum - Roman D. Gerasimov; Arseny D. Starikov (Известия Томского политехнического университета: Промышленная кибернетика)
Relevance. Today data processing is an integral process when conducting a physical experiment, at the same time, as a rule, specialized software is supplied only with expensive equipment and it is not available to the average researcher. Specialists in the field of materials science use a significant number of different programs to process data, in particular, generated by X-ray diffractometers, electron microscopes and other types of instruments. As a rule, different manufacturers use different formats of data representation, processing of which is performed by specialists who understand hardware limitations, physical principles of analysis, as well as possible inaccuracies and errors, interpretation often requires the formation of hypotheses. As a rule, the operator of each individual device is not an expert in a narrowly defined subject area, so it is difficult to say, which pieces of data are important for the user (customer). Consolidation of data from various sources allows you to reduce the amount of time for analyzing experimental results; the amount of necessary software used for analysis allows you to improve the quality of the analysis. It is often possible to find implicit patterns. In this regard, it seems relevant to create a module for collecting and storing data on experiments and results of analysis by various methods. In addition, in conditions of complexity of procurement procedures for specialized software, the issue of creating domestic solutions seems relevant. X-ray phase analysis is widespread. In this regard, this work demonstrates the results of creating a software module for an electronic journal of experiments, which allows you to estimate the positions of diffraction maxima, i.e. to carry out rapid analysis of laboratory samples obtained during the experiments. Aim. To develop a digital solution for centralized storage of experimental data related to the production of solid crystalline materials and for primary analysis. Object. X-ray diffraction patterns. Subject. To determine the position of the reflection on the diffraction pattern. Methods. Analysis and evaluation of already developed solutions, as well as existing literature; testing of existing algorithms for data analysis, finding diffraction maxima on the diffractogram. Results. The authors have developed the module for the primary profile analysis of diffraction patterns for an electronic journal. This module makes it possible to approximately determine the intensity and positions of diffraction maxima, from which the phase composition of the powders under study can be determined, and with known corundum numbers, the quantitative composition can be determined. This module was compared to the commonly used software. The developed digital solution allows reducing the time for analyzing experimental data, the amount of software used, simplifying determination of the phase composition of synthesized powders within a series, and increasing the efficiency of experiments and research. Thus, the developed solution is a relevant and sought-after tool for researchers involved in the synthesis of solid crystalline materials.